2022
DOI: 10.3390/w14050771
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Oxygen Volumetric Mass Transfer in a Geometrically Constrained Vortex

Abstract: Aeration is one of the most cost intensive steps in water and wastewater treatment due to the large energy requirement for the creation of large surfaces for sufficient gas exchange as well as for providing efficient liquid transport in order to exchange saturated liquid elements at the surface with unsaturated ones from the bulk. In this work we show that geometrically constrained vortices in a hyperbolic funnel are a promising aeration technique as they meet these criteria and allow oxygen transfer coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…One innovative technology in this field is the water vortex gas discharge plasma reactor, which combines plasma technology with a Schauberger hyperbolic vortex. As shown in [36,37] water vortices are very efficient aeration systems, and thus are capable of dissolving gases at very high rates. This reactor enables the in-situ production of reactive species in the gas phase for micropollutant degradation by plasma discharge and the efficient mass transfer and mixing required for distributing these reactive species into the liquid phase by the water vortex.…”
Section: Plasma Treatmentmentioning
confidence: 99%
“…One innovative technology in this field is the water vortex gas discharge plasma reactor, which combines plasma technology with a Schauberger hyperbolic vortex. As shown in [36,37] water vortices are very efficient aeration systems, and thus are capable of dissolving gases at very high rates. This reactor enables the in-situ production of reactive species in the gas phase for micropollutant degradation by plasma discharge and the efficient mass transfer and mixing required for distributing these reactive species into the liquid phase by the water vortex.…”
Section: Plasma Treatmentmentioning
confidence: 99%
“…Therefore, to increase the efficiency of this process, it is necessary either to increase the gas concentration gradient or the volumetric motion of the liquid.The latter directly depends on the turbulence of the system in the form of Taylor-like vortices, which facilitate the transport of saturated fluid elements from the interface into the bulk liquid. In another work on this topic9 , the main parameters for different vortex regimes, such as the water flow rate, K L a 20 , and SOTR, were compared. This study showed great promise for this technology because the system enables very fast gas transfer compared to other methods that are used for water aeration.The purpose of this article is to provide and demonstrate this method for creating different water vortex regimes in hyperbolic Schauberger funnels (small: 26 cm high and 15 cm top diameter; medium: 94 cm high and 30 cm top diameter; large: 153 cm high and 59 cm top diameter) with the goal of efficient water aeration.Protocol 1.…”
mentioning
confidence: 99%
“…There was an omission in the original publication [1]. The authors showed SOTR values in a figure but did not mention how these values were calculated.…”
mentioning
confidence: 99%